Taxonomy, phylogeny and biogeography of cisticolas (Cisticola spp.) - Davies, Owen R (Percy FitzPatrick Institute of African Ornithology, 2015)
A review of the genus Cisticola was published in 1930 by Rear-admiral Lynes. While subsequent authors have modified Lynes' original groupings, his work remains the basis for modern syntheses of cisticolas. This study tests Lynes' hypotheses by analysing data that he presented in his review and with measurement and plumage data collected from museum specimens. Lynes' groupings were well recovered (98%) when data captured from his review were analysed phenetically, suggesting that he grouped species mostly by similarity. In contrast, when morpho-behavioural data were analysed using cladistic methods, many of his groupings were not monophyletic and the resultant cladogram had very little nodal support due to their highly conservative morphology. To resolve the structure of the genus and the relationships within it, two mitochondrial and four nuclear regions were sequenced from toe-pad samples taken from museum specimens. The molecular analyses included 44 of the 49 currently recognised species and represents the most taxon-dense molecular phylogeny of the genus. The resultant phylogeny separates species into five main clades, but many of Lynes' groupings were not monophyletic and there was also very little support for more recent groupings. Vocalisation analyses indicated that frequency components of songs were correlated with habitat type and body size. These correlations, though, disappeared when phylogeny was controlled for indicating that phylogenetic history rather than habitat preference influenced song character distribution. Some song types are mismatched to their environment, and some sympatric sister species appear to give similar calls. Cisticolas may overcome these attenuation and identification difficulties with behavioural adaptations and aerial displays. The biogeographic distribution of closely related species does not agree with many of the previously proposed hypotheses and a dated phylogeny estimates that most of the diversification in the genus has occurred within the last five million years. Most of the mean divergence date estimates correlated with periods of climate variability and episodes during which there is evidence for high lake levels in Africa, rather than correlating with Plio-Pleistocene glaciation, offering evidence that open habitats may have become fragmented during extremes of both arid and humid climates.